Portaria PRR5 nº 92, de 6 de junho de 2017 - Marcelo Alves Dias de Souza (DOU, Brasília, DF, 8 jun. 2017, Seção 2, p. 58., 2017)
Apostilar a publicação de nomeação de servidora para o cargo em comissão de Assessor.